Bifidobacterium breve Exopolysaccharide Blocks Dendritic Cell Maturation and Activation of CD4+ T Cells - Hickey, Ana; Stamou, Panagiota; Udayan, Sreeram; Ramón-Vázquez, Ana; Esteban-Torres, Maria; Bottacini, Francesca; Woznicki, Jerzy Adam; Hughes, Owen; Melgar, Silvia; Ventura, Marco; Van Sinderen, Douwe; Rossini, Valerio; et al. (Frontiers in Microbiology, 2021)
Exopolysaccharide (EPS) is a bacterial extracellular carbohydrate moiety which has been associated with immunomodulatory activity and host protective effects of several gut commensal bacteria. Bifidobacterium breve are early colonizers of the human gastrointestinal tract (GIT) but the role of EPS in mediating their effects on the host has not been investigated for many strains. Here, we characterised EPS production by a panel of human B. breve isolates and investigated the effect of EPS status on host immune responses using human and murine cell culture-based assay systems. We report that B. breve EPS production is heterogenous across strains and that immune responses in human THP-1 monocytes are strain-specific, but not EPS status-specific. Using wild type and isogenic EPS deficient mutants of B. breve strains UCC2003 and JCM7017 we show that EPS had strain-specific divergent effects on cytokine responses from murine bone marrow derived macrophages (BMDMs) and dendritic cells (BMDCs). The B. breve UCC2003 EPS negative (EPS-) strain increased expression of cytokine genes (Tnfa, Il6, Il12a, Il23a) relative to untreated BMDCs and BMDCs treated with wild type strain. B. breve UCC2003 and JCM7017 EPS- strains increased expression of dendritic cell (DC) activation and maturation marker genes (Cd80, Cd83, Cd86) relative to untreated BMDCs. Consistent with this, BMDCs co-cultured with B. breve UCC2003 and JCM7017 EPS- strains engineered to express OVA antigen activated OVA-specific OT-II CD4+ T-cells in a co-culture antigen-presentation assay while EPS proficient strains did not. Collectively, these data indicate that B. breve EPS proficient strains use EPS to prevent maturation of DCs and activation of antigen specific CD4+ T cells responses to B. breve. This study identifies a new immunomodulatory role for B. breve EPS and suggests it may be important for immune evasion of adaptive immunity by B. breve and contribute to host-microbe mutualism.